Evaluation of ber (Ziziphus mauritiana) germplasm for fruit setting characters (Current Horticulture, 2024)
The study was carried out to evaluate variability between different ber (Ziziphus mauritiana Lamk.) germplasm on the basis  of flowering and fruit setting. Significant variability was observed for the recorded parameters. Bawal Ber 12 exhibited early  initiation, while BS 3 showed delayed flower initiation. The shortest flowering duration was recorded in Bawal Ber 9 (37 days),  whereas longest flowering duration was recorded in Bawal Ber 1, Bawal Ber 5 and BS 1 (42 days). Different germplasm displayed  notable variation in mature fruit colour, including greenish-yellow, yellow and green. Oval shaped fruits were observed in Bawal  Ber 1, Bawal Ber 9 and BS 3 while Bawal Ber 2, Bawal Ber 5, Bawal Ber 6, Bawal Ber 7, Bawal Ber 8, Bawal Ber 10 and BS 2 exhibited  ovate shape. Bawal Ber 3, Bawal Ber 4 and BS 1 had oblong fruits and Bawal Ber 11 displayed an oblate shape whereas Bawal Ber  12 had round fruits. The stone shape of ber germplasm varied with some exhibiting a spindle, oblong, club or oval shape. Bawal  Ber 1, Bawal Ber 2, Bawal Ber 3, Bawal Ber 4, Bawal Ber 5, Bawal Ber 7, Bawal Ber 9, Bawal Ber 10 and Bawal Ber 12 had a plain  fruit surface, while Bawal Ber 6, Bawal Ber 8, Bawal Ber 11, BS 1, BS 2 and BS 3 showed a ridged and wart fruit surface.
Keywords: Ber; Fruit setting; Colour; Flowering; Oval; Ovate; Ridged; Variability